Influence of different functionalized CdTe quantum dots on the accumulation of metals, developmental toxicity and respiration in different development stages of the zebrafish (Danio rerio) - Bosch, Suanne; Botha, Tarryn Lee; Wepener, Victor (Frontiers in Toxicology, 2023)
The bioaccumulation and differential effects of cadmium tellurium quantum dot (CdTe QDs) nanomaterials with different functional groups are poorly understood in aquatic organisms. Studies were conducted to establish metal uptake, developmental effects and respiration effects using zebrafish as model organisms. Zebrafish embryos were exposed to carboxylate (COOH), ammonia (NH3), and polyethylene glycol (PEG) functionalized CdTe QDs at nominal concentrations of 0.5, 2, 4, 6 and 20 mg QDs/L. Except for the QD-NH3 treatment, metal uptake in the larvae was not dose-dependent. The total Cd or Te concentrations in the larvae could not be explained by the metal concentrations or dissolution of the materials in the exposure media. The most severe effects were seen in the QD-NH3 treatments where the highest exposure concentration caused respiration inhibition and the low concentrations caused hatching delays and severe malformations. The toxicities observed in the low concentrations are attributed to particles crossing the pores in the chorion eliciting effects, and toxicities at the higher concentrations are linked to the aggregation of particle agglomerates to the surface of the chorion impairing respiration. Developmental defects were recorded following exposure to all three functional groups, but the QD-NH3 group had the most severe response. The LC50 values for embryo development of QD-COOH and QD-PEG groups were higher than 20 mg/L and the LC50 of the QD-NH3 group was 20 mg/L.